Scapular motor control and upper limb movement quality in subjects with and without chronic shoulder pain - Melo, Ana (2024)
Despite the existence of several studies about the scapula’s position and motion, in shoulder pain conditions, there are still conflicting findings regarding scapular adaptations and reduced research about the scapula’s role during functional tasks. The present study aimed to compare scapular-related kinematic and electromyographic outcomes during different shoulder movements (with and without load) and the drinking task, between symptomatic and asymptomatic subjects. Forty subjects (divided into two groups) participated in this cross-sectional observational study. Scapulothoracic motion, scapulohumeral rhythm, and movement quality (considering trunk compensation, time-to-peak acceleration, and smoothness), as well as the relative surface electromyographic activity and muscle ratio considering the trapezius, serratus anterior, and levator scapulae (LS), were assessed. The symptomatic group presented the following: (1) changes in scapular upward rotation (p = 0.008) and winging (p = 0.026 and p = 0.005) during backward transport and drink phases; (2) increased muscle activity level of the middle trapezius (MT) in all tasks (p < 0.0001 to p = 0.039), of LS during shoulder elevation with load (p = 0.007), and of LS and LT during most of the drinking task phases (p = 0.007 to p = 0.043 and p < 0.0001 to p = 0.014, respectively); (3) a decreased serratus anterior lower portion activity level (SAlow) during shoulder lowering with load (p = 0.030) and drink phase (p = 0.047); and (4) an increased muscular ratio between scapular abductors/adductors (p = 0.005 to p = 0.036) and elevators/depressors (p = 0.008 to p = 0.028). Compared to asymptomatic subjects, subjects with chronic shoulder pain presented scapular upward rotation and winging adaptations; increased activity levels of MT, LT, and LS; decreased activity levels of SAlow; and increased scapular muscle ratios.